Reduced mitochondrial DNA and OXPHOS protein content in skeletal muscle of children with cerebral palsy. (27th June 2021) - von Walden, Ferdinand; Vechetti, Ivan J; Englund, Davis; Figueiredo, Vandré C; Fernandez‐Gonzalo, Rodrigo; Murach, Kevin; Pingel, Jessica; Mccarthy, John J; Stål, Per; Pontén, Eva
Abstract : Aim: To provide a detailed gene and protein expression analysis related to mitochondrial biogenesis and assess mitochondrial content in skeletal muscle of children with cerebral palsy (CP). Method: Biceps brachii muscle samples were collected from 19 children with CP (mean [SD] age 15y 4mo [2y 6mo], range 9–18y, 16 males, three females) and 10 typically developing comparison children (mean [SD] age 15y [4y], range 7–21y, eight males, two females). Gene expression (quantitative reverse transcription polymerase chain reaction [PCR]), mitochondrial DNA (mtDNA) to genomic DNA ratio (quantitative PCR), and protein abundance (western blotting) were analyzed. Microarray data sets (CP/aging/bed rest) were analyzed with a focused query investigating metabolism‐ and mitochondria‐related gene networks. Results: The mtDNA to genomic DNA ratio was lower in the children with CP compared to the typically developing group (−23%, p =0.002). Out of five investigated complexes in the mitochondrial respiratory chain, we observed lower protein levels of all complexes (I, III, IV, V, −20% to −37%; p <0.05) except complex II. Total peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC1α) messenger RNA ( p <0.004), isoforms PGC1α1 ( p =0.05), and PGC1α4 ( p <0.001) were reduced in CP. Transcriptional similarities were observed between CP, aging, and 90 days' bed rest. Interpretation: Mitochondrial biogenesis, mtDNA, and oxidative phosphorylation protein content are reduced in CP muscle compared with typically developing muscle. Transcriptional pathways shared between aging and long‐term unloading suggests metabolic dysregulation in CP, which may guide therapeutic strategies for combatting CP muscle pathology. What this paper adds Cerebral palsy (CP) muscle contains fewer energy‐generating organelles than typically developing muscle. Gene expression in CP muscle is similar to aging and long‐term bed rest. What this paper adds: Cerebral palsy (CP) muscle contains fewer energy‐generating organelles than typically developing muscle. Gene expression in CP muscle is similar to aging and long‐term bed rest. We compared skeletal muscle samples from children with cerebral palsy (CP) and typically developing children and observed evidence of reduced mtDNA and OXPHOS protein content in CP skeletal muscle, indicating reduced mitochondrial abundance. Moreover, transcriptional similarities to aging and long‐term unloading suggests signs of metabolic alterations in CP skeletal muscle.